2005
DOI: 10.1124/jpet.105.089169
|View full text |Cite
|
Sign up to set email alerts
|

A-770041, a Novel and Selective Small-Molecule Inhibitor of Lck, Prevents Heart Allograft Rejection

Abstract: Lck, one of eight members of the Src family of tyrosine kinases, is activated after T cell stimulation and is required for T-cell proliferation and interleukin (IL)-2 production. Inhibition of Lck has been a target to prevent lymphocyte activation and acute rejection. Here, we report the pharmacologic characterization of 1-methyl-1H-indole-2-carboxylic acid, an orally bioavailable pyrazolo [3,4-d]pyrimidine with increased selectivity for Lck compared with previously reported compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 24 publications
(32 reference statements)
1
43
1
Order By: Relevance
“…P59Fyn phosphorylates tyrosines on the substrate and activates and recruits ZAP-70, which phosphorylates SLP-76 joint protein to activate the Ras-Mitogen path which activates IP3, DG second message path [17][18][19]. These experimental results showed that in the early stage of transplantation, unlike CD4 and CD8 mRNA expression, P59Fyn mRNA was in a hyperactivation state at 72 h, which was independent of CD4 and CD8 gene transcription in the control group.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…P59Fyn phosphorylates tyrosines on the substrate and activates and recruits ZAP-70, which phosphorylates SLP-76 joint protein to activate the Ras-Mitogen path which activates IP3, DG second message path [17][18][19]. These experimental results showed that in the early stage of transplantation, unlike CD4 and CD8 mRNA expression, P59Fyn mRNA was in a hyperactivation state at 72 h, which was independent of CD4 and CD8 gene transcription in the control group.…”
Section: Discussioncontrasting
confidence: 54%
“…However, many reports showed that acute rejection occurred after medication [15][16][17]. We wanted to observe the effects of cyclosporine A on lymphocyte proteins, gene expression kinetics and pathological changes occurring after heart transplant.…”
Section: Discussionmentioning
confidence: 98%
“…This may be the most relevant finding in our results because it opens the opportunity to titrate concentrations of each individual drug below toxicity levels while maintaining the ability to quell aberrant T-cell activation. Further studies combining Lck inhibitors, such as dasatinib or the recently described A-770041, 43,44 with costimulatory blockade may also provide new routes to achieve desired levels of immunomodulation while minimizing side effects. Therefore, new dosing schedules could be developed to optimize SFK inhibition in the context of concurrent NFAT, mTOR, or JAK inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm this observation by an independent approach, we applied a chemical inhibitor of Lck, A-770041, on wild-type (WT) Jurkat cells (41). This chemical compound is 300-fold more selective against Lck (IC 50 ϭ 147 nM) than against Fyn (IC 50 ϭ 44.1 M), another Src family tyrosine kinase involved in T cell signaling (41). As expected, the calcium influx induced by gal-9 was markedly reduced by increasing concentrations of Lck inhibitor and was totally abolished with 170 nM (Fig.…”
Section: Induction Of Early Calcium Mobilization By Exogenous Gal-9 Inmentioning
confidence: 98%
“…Therefore, Lck seemed important for the gal-9 transduction pathway. To confirm this observation by an independent approach, we applied a chemical inhibitor of Lck, A-770041, on wild-type (WT) Jurkat cells (41). This chemical compound is 300-fold more selective against Lck (IC 50 ϭ 147 nM) than against Fyn (IC 50 ϭ 44.1 M), another Src family tyrosine kinase involved in T cell signaling (41).…”
Section: Induction Of Early Calcium Mobilization By Exogenous Gal-9 Inmentioning
confidence: 98%